Faith-Based Organizations and Veteran Reintegration Enriching the Web of Support - Werber, Laura (RAND Corporation, 2015)
Faith-based organizations (FBOs) are an important resource for veterans as they readjust to civilian life. Interviews show that FBOs not only help veterans with spiritual matters but address diverse areas of veteran health and well-being. Although FBO reintegration support is unique and even preferred at times, there are limits to what they can do. This report suggests ways to better integrate them into the web of support.